Effect of gamma irradiation and modified atmosphere packaging on the quality and storage stability of sweet cherry (cv. Misri and Double) under ambient and refrigerated storage conditions - Wani, Shahnaz Parveen; Mir, M A; Hameed, Omar Bin; Hussain, P R; Majeed, Darakshan (Journal of Postharvest Technology, 2018)
Gamma irradiation in combination with modified atmosphere packaging (MAP) was tested for maintaining the storage quality and extending shelf life of sweet cherries. Sweet cherry (cv. Misri and Double) after harvest was modified atmosphere packaged and subjected to the irradiation dose of 0.3, 0.6, 0.9, 1.2 and 1.5 kGy. The treated fruits including control was stored under ambient (temperature 25±2 °C, RH 70%) and refrigerated (temperature 3 ±1 °C, RH 80%) conditions. Irradiation at 1.2 kGy and MAP gave 9 and 28 d extension in shelf life of pear under ambient and refrigerated storage conditions, respectively. All combinatory treatments delayed the decaying of fruit during post refrigerated storage, but combination of MAP and 1.2 kGy irradiation proved significantly (P ≤ 0.05) effective in maintaining the storage quality and delaying the decaying of pear.